2012
DOI: 10.1073/pnas.1213726109
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for recognition of methylated and specific DNA sequences by the zinc finger protein Kaiso

Abstract: Methylation of CpG dinucleotides in DNA is a common epigenetic modification in eukaryotes that plays a central role in maintenance of genome stability, gene silencing, genomic imprinting, development, and disease. Kaiso, a bifunctional Cys 2 His 2 zinc finger protein implicated in tumor-cell proliferation, binds to both methylated CpG (mCpG) sites and a specific nonmethylated DNA motif (TCCTGCNA) and represses transcription by recruiting chromatin remodeling corepression machinery to target genes. Here we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
164
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(167 citation statements)
references
References 34 publications
(56 reference statements)
3
164
0
Order By: Relevance
“…Some crystal structures of proteins that specifically recognize methylated DNA have recently become available (Buck-Koehntop et al, 2012;Liu et al, 2014). The detailed analysis of the binding modes revealed that although similarities between them exist (Liu et al, 2013), it is yet unclear why three distinct families of methylated DNA-binding proteins were needed in the course of evolution.…”
Section: Impact Of Cytosine Methylation On Dna-protein Interactionsmentioning
confidence: 99%
“…Some crystal structures of proteins that specifically recognize methylated DNA have recently become available (Buck-Koehntop et al, 2012;Liu et al, 2014). The detailed analysis of the binding modes revealed that although similarities between them exist (Liu et al, 2013), it is yet unclear why three distinct families of methylated DNA-binding proteins were needed in the course of evolution.…”
Section: Impact Of Cytosine Methylation On Dna-protein Interactionsmentioning
confidence: 99%
“…It contains an amino-terminal BTB/POZ (BR-C, ttk and bab/Pox virus and Zn finger) domain involved in protein -protein interactions and three mCG-DNA-binding carboxy-terminal zinc fingers (Cys 2 His 2 coordination) that repress transcription by recruiting chromatin-remodeling compression machinery to target genes (reviewed in Clouaire and Stancheva 2008). Recently, structural studies of the zinc-finger domains of Kaiso bound to a pair of sequential symmetrically methylated 5mCpG/5mCpG DNA sites from the E-cadherin promoter region have elucidated the details underlying the recognition process, in which 1 Kaiso molecule is bound per DNA duplex (Buck-Koehntop et al 2012). The side chains of the first two zinc fingers target the major groove through base-specific recognition mediated by classical and C-H † †O hydrogen bonds, as well as phosphate backbone contacts.…”
Section: Methylcytosine-binding Zn-finger Proteinsmentioning
confidence: 99%
“…The ability of ZnF proteins to respond to methylation in this way is significant because ''sequences longer than CpG would be necessary for the regulation of gene expression by methylation'' (Holliday 1996). The structures of three ZnF domains bound to 5mC-containing DNA were solved recently from the transcription factors Kaiso, Zfp57, and Klf4 (Buck-Koehntop et al 2012;Liu et al 2012Liu et al , 2014. Here we investigate the binding of ZnF domains to oxidized modifications of 5mC.…”
mentioning
confidence: 99%